Age-hardened high-temperature alloy powder for 3D printing and its preparation method and application
By increasing the content of MO and ZR elements, the 3D printing of NB, Al, and TI element content is reduced, and the time -effective high -temperature alloy powder is used to solve the problem of poor plasticity of high -temperature alloy printing samples in existing technologies. Significant improvement and intensity performance.
Patent Information
- Application Number
- CN202211673846.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-26
AI Technical Summary
The aging-reinforced high-temperature alloy printed samples produced in the prior art have a problem of poor plasticity, especially at high temperatures.
By increasing the content of MO elements and ZR elements, reducing the content of NB elements, AL elements, and TI elements, preparing a 3D printing of 3D printing with a specific chemical component, and the time -effective high -temperature alloy powder is used. Essence
It significantly improves the stretching properties, especially the high temperature (650 ° C) stretching properties, and takes into account the strength performance.
Smart Images

Figure CN116121598B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of additive manufacturing technology, and specifically, to age-hardened high-temperature alloy powder for 3D printing, a preparation method thereof, and applications thereof; more specifically, to age-hardened high-temperature alloy powder for 3D printing, a preparation method thereof, a 3D printing method, and a 3D printed part. Background Art
[0002] 3D printing is a type of rapid prototyping technology, also known as additive manufacturing. It is a technology that uses digital model files as the basis and uses bondable materials such as powdered metal or plastic to construct objects by printing layer by layer.
[0003] Age-hardened nickel-based high-temperature alloys have high strength at -196°C and high temperatures of 600-700°C, and also have excellent resistance to oxidative corrosion in oxygen-rich atmospheres.
[0004] However, the age-hardened high-temperature alloy printed samples obtained in the prior art have the problem of poor plasticity.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first purpose of the present invention is to provide an aging-hardened high-temperature alloy powder for 3D printing, which adopts a specific chemical composition, especially increases the content of Mo and Zr elements, reduces the content of Nb, Al and Ti elements, improves tensile plasticity, and especially significantly improves high-temperature tensile plasticity.
[0007] The second object of the present invention is to provide a method for preparing aging-hardened high-temperature alloy powder for 3D printing.
[0008] A third object of the present invention is to provide a 3D printing method.
[0009] A fourth object of the present invention is to provide a 3D printed part.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The invention provides an aging-strengthening high-temperature alloy powder for 3D printing. The chemical composition of the aging-strengthening high-temperature alloy powder for 3D printing includes, by mass percentage, C≤0.05%, Cr 14.5%-18.5%, Mo 4.5%-6.0%, Nb 3.5%-4.5%, Ti 0.1%-0.7%, Al 1.2%-2.0%, Fe 12%-16%, V 0.3%-0.6%, Cu 0.1%-1.0%, Mn≤0.5%, Si≤0.5%, Zr 0.05%-0.3%, Ce≤0.01%, B≤0.01%, S≤0.015%, P≤0.015%, and the balance is Ni.
[0012] Preferably, the chemical composition of the aging-hardened high-temperature alloy powder for 3D printing includes, by mass percentage: C≤0.05%, Cr 14.5%~18.5%, Mo 5.0%~6.0%, Nb3.5%~4.5%, Ti 0.1%~0.6%, Al 1.2%~2.0%, Fe 12%~16%, V 0.3%~0.6%, Cu 0.6%~1.0%, Mn≤0.5%, Si≤0.5%, Zr 0.15%~0.3%, Ce≤0.01%, B≤0.01%, S≤0.015%, P≤0.015%, and the balance is Ni.
[0013] Preferably, the chemical composition of the aging-hardened high-temperature alloy powder for 3D printing includes, by mass percentage: C≤0.05%, Cr 14.5%~18.5%, Mo 5.2%~6.0%, Nb3.5%~4.1%, Ti 0.1%~0.5%, Al 1.2%~1.6%, Fe 12%~16%, V 0.3%~0.6%, Cu 0.6%~1.0%, Mn≤0.5%, Si≤0.5%, Zr 0.2%~0.3%, Ce≤0.01%, B≤0.01%, S≤0.015%, P≤0.015%, and the balance is Ni.
[0014] The present invention also provides a method for preparing the aging-hardened high-temperature alloy powder for 3D printing as described above, comprising the following steps:
[0015] After being prepared according to the mass percentage as described above, the prepared metal powder is vacuum melted to obtain molten metal liquid;
[0016] The molten metal liquid is atomized and powdered to obtain the aging-strengthened high-temperature alloy powder for 3D printing.
[0017] Preferably, the vacuum melting temperature is 1670-1690°C;
[0018] Preferably, the vacuum degree during the vacuum melting process is 7-9Pa.
[0019] Preferably, the atomization pressure during the atomization powder spraying process is 3.7-3.9 MPa.
[0020] The present invention also provides a 3D printing method of the age-hardened high-temperature alloy powder for 3D printing as described above, wherein the 3D printing includes laser powder bed melting additive manufacturing.
[0021] Preferably, the laser power of the 3D printing is 280-290W;
[0022] Preferably, the laser scanning speed of the 3D printing is 940-990 mm / s;
[0023] Preferably, the laser energy density of the 3D printing is 65-70 J / mm 3 .
[0024] The present invention also provides a 3D printed part obtained by the 3D printing method of the aging-hardened high-temperature alloy powder for 3D printing as described above.
[0025] Preferably, the elongation after fracture of the 3D printed part at 650° C. is ≥13%, and the shrinkage after fracture of the 3D printed part is ≥22%;
[0026] Preferably, the elongation after fracture of the 3D printed part at 650° C. is ≥18%, and the shrinkage after fracture of the 3D printed part is ≥25%.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The aging-hardened high-temperature alloy powder for 3D printing provided by the present invention improves tensile plasticity, especially high-temperature (650°C) tensile plasticity, by adopting a specific chemical composition, such as increasing the content of Mo and Zr elements and reducing the content of Nb, Al and Ti elements.
[0029] (2) The specific 3D printing parameters provided by the present invention further improve the high-temperature tensile plasticity while taking into account the strength performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is a tissue morphology diagram of a sample obtained by 3D printing according to Example 1 of the present invention;
[0032] Figure 2 This is a tissue morphology diagram of a sample obtained by 3D printing according to Example 2 of the present invention;
[0033] Figure 3 This is a tissue morphology diagram of a sample obtained by 3D printing according to Example 3 of the present invention;
[0034] Figure 4 This is a tissue morphology diagram of the sample obtained by 3D printing in Comparative Example 1 of the present invention;
[0035] Figure 5 This is a tissue morphology diagram of a sample obtained by 3D printing in Comparative Example 2 of the present invention;
[0036] Figure 6 This is an optical microscope image of the sample obtained by 3D printing in Example 1 of the present invention;
[0037] Figure 7 This is an optical microscope image of a sample obtained by 3D printing according to Example 4 of the present invention;
[0038] Figure 8 This is an optical microscope image of a sample obtained by 3D printing in Example 5 of the present invention;
[0039] Fig. 9 This is an optical microscope image of a sample obtained by 3D printing according to Example 6 of the present invention;
[0040] Fig.10 This is an optical microscope image of the sample obtained after 3D printing in Example 7 of the present invention. DETAILED DESCRIPTION
[0041] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0042] In a first aspect, the present invention provides an aging-hardened high-temperature alloy powder for 3D printing, specifically an aging-hardened nickel-based high-temperature alloy powder for 3D printing, wherein the chemical composition comprises, by mass percentage, C≤0.05%, Cr14.5%~18.5%, Mo 4.5%~6.0%, Nb3.5%~4.5%, Ti 0.1%~0.7%, Al 1.2%~2.0%, Fe 12%~16%, V 0.3%~0.6%, Cu 0.1%~1.0%, Mn≤0.5%, Si≤0.5%, Zr0.05%~0.3%, Ce≤0.01%, B≤0.01%, S≤0.015%, P≤0.015%, and the balance is Ni.
[0043] The present invention uses aging-hardened high-temperature alloy powder for 3D printing with a specific chemical composition, especially increasing the content of Mo and Zr elements and reducing the content of Nb, Al and Ti elements, thereby improving tensile plasticity, especially high-temperature tensile plasticity, and solving the problem of poor plasticity of conventional aging-hardened high-temperature alloy printed samples.
[0044] Specifically, the microstructure of the aging-strengthened high-temperature alloy powder for 3D printing provided by the present invention mainly includes γ matrix, γ' phase and carbide. Among them, the Mo element mainly plays a role of solid solution strengthening in the alloy, and the Zr element is a trace element, which mainly exists in the γ' phase in the alloy powder and improves the stability and re-dissolution temperature of the γ' phase; the reduction of Nb, Al and Ti elements reduces the content of γ' phase in the alloy powder, but the increase of Mo and Zr elements further makes up for the room temperature and high temperature strength of the alloy powder.
[0045] The mass percentage of C includes but is not limited to any one of 0.01%, 0.02%, 0.03%, 0.04% or any range between them; the mass percentage of Cr includes but is not limited to any one of 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18% or any range between them; the mass percentage of Mo includes but is not limited to any one of 4.8%, 5%, 5.3%, 5.5%, 5.8% or any range between them; N The mass percentage of b includes but is not limited to any one of 3.6%, 3.8%, 4.0%, 4.2% or any range between them; the mass percentage of Ti includes but is not limited to any one of 0.2%, 0.3%, 0.4%, 0.45%, 0.5%, 0.6% or any range between them; the mass percentage of Al includes but is not limited to any one of 1.3%, 1.5%, 1.55%, 1.6%, 1.7%, 1.8%, 1.9% or any range between them The mass percentage of Fe includes but is not limited to any point value of 13%, 13.5%, 14%, 14.5%, 15% or any range value between the two; the mass percentage of V includes but is not limited to any point value of 0.4%, 0.45%, 0.5%, 0.55% or any range value between the two; the mass percentage of Cu includes but is not limited to any point value of 0.2%, 0.4%, 0.5%, 0.6%, 0.8% or any range value between the two; the mass percentage of Mn includes but is not limited to any point value of 0.2%, 0.4%, 0.5%, 0.6%, 0.8% or any range value between the two; The mass percentage of Si includes but is not limited to any one of 0.002%, 0.005%, 0.01%, 0.1%, 0.3% or any range between them; the mass percentage of Zr includes but is not limited to any one of 0.005%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.25% or any range between them.
[0046] In order to further comprehensively consider the shaping and strength properties, the present invention optimizes the amount of each element in the aging-strengthening high-temperature alloy powder for 3D printing. Preferably, the chemical composition of the aging-strengthening high-temperature alloy powder for 3D printing includes, by mass percentage: C≤0.05%, Cr 14.5%~18.5%, Mo 5.0%~6.0%, Nb 3.5%~4.5%, Ti 0.1%~0.6%, Al1.2%~2.0%, Fe 12%~16%, V 0.3%~0.6%, Cu 0.6%~1.0%, Mn≤0.5%, Si≤0.5%, Zr 0.15%~0.3%, Ce≤0.01%, B≤0.01%, S≤0.015%, P≤0.015%, and the balance is Ni.
[0047] More preferably, the chemical composition of the aging-hardened high-temperature alloy powder for 3D printing includes, by mass percentage: C≤0.05%, Cr 14.5%~18.5%, Mo 5.2%~6.0%, Nb3.5%~4.1%, Ti 0.1%~0.5%, Al 1.2%~1.6%, Fe 12%~16%, V 0.3%~0.6%, Cu 0.6%~1.0%, Mn≤0.5%, Si≤0.5%, Zr 0.2%~0.3%, Ce≤0.01%, B≤0.01%, S≤0.015%, P≤0.015%, and the balance is Ni.
[0048] In a second aspect, the present invention provides a method for preparing the aging-hardened high-temperature alloy powder for 3D printing as described above, comprising the following steps:
[0049] After being prepared according to the mass percentage as described above, the prepared metal powder is vacuum melted to obtain molten metal liquid;
[0050] The molten metal liquid is atomized and powdered to obtain the aging-strengthened high-temperature alloy powder for 3D printing.
[0051] The invention adopts vacuum melting gas atomization technology, which has the advantages of small powder particle size, high purity, low oxygen content and high shape.
[0052] In some specific embodiments of the present invention, the preparation method of the aging-hardened high-temperature alloy powder for 3D printing specifically includes: preparing according to the mass percentage as described above, loading the prepared metal powder into a smelting furnace, and evacuating the smelting furnace; adjusting the medium frequency voltage for vacuum smelting; refining and degassing; turning on the tundish heating system of the atomizing device, passing high-purity argon gas, pouring the molten metal into the tundish, and entering the guide tube and nozzle, at which time the molten metal flow is atomized by the high-pressure gas flow for atomization powder spraying; the atomized metal powder solidifies and settles in the atomizing tower, falls into the powder tank, collects the powder, and obtains the aging-hardened high-temperature alloy powder for 3D printing.
[0053] Preferably, the vacuum melting temperature is 1670-1690°C, including but not limited to any one of 1675°C, 1680°C, 1685°C or a range between any two of them.
[0054] Preferably, the vacuum degree in the vacuum melting process is 7-9 Pa, including but not limited to any one of 7.5 Pa, 8 Pa, 8.5 Pa or a range between any two of them.
[0055] In some specific embodiments of the present invention, the vacuum melting time is 60 to 80 minutes, including but not limited to any one of 65 minutes, 70 minutes, and 75 minutes, or a range between any two of them.
[0056] Preferably, the atomization pressure during the atomization powder spraying process is 3.7-3.9 MPa, including but not limited to any one of 3.75 MPa, 3.8 MPa, 3.85 MPa or a range between any two of them.
[0057] In a third aspect, the present invention provides a 3D printing method of the age-hardened high-temperature alloy powder for 3D printing as described above, wherein the 3D printing includes laser powder bed melting additive manufacturing.
[0058] Preferably, the laser power of the 3D printing is 280-290W, including but not limited to any point value of 282W, 285W, 288W or a range value between any two of them.
[0059] Preferably, the laser scanning speed of the 3D printing is 940-990 mm / s, including but not limited to any point value of 950 mm / s, 960 mm / s, 970 mm / s, 980 mm / s or a range value between any two of them.
[0060] Preferably, the laser energy density of the 3D printing is 65-70 J / mm 3 Including but not limited to 66J / mm3 、67J / mm 3 、68J / mm 3 、69J / mm 3 Any point value in or any range of values between them.
[0061] The present invention further improves the tensile plasticity, especially the high-temperature tensile plasticity, and takes into account the strength performance by adopting specific 3D printing parameters.
[0062] In a fourth aspect, the present invention provides a 3D printed part produced by the 3D printing method of the age-hardened high-temperature alloy powder for 3D printing as described above.
[0063] Preferably, the elongation after fracture of the 3D printed part at 650°C is ≥13%, including but not limited to any point value of 14%, 15%, 16%, 17%, 18%, 19%, 20% or any range value between two of them. The shrinkage after fracture of the 3D printed part is ≥22%; including but not limited to any point value of 23%, 24%, 25%, 26%, 27%, 28% or any range value between two of them.
[0064] The 3D printed part provided by the present invention has higher high-temperature elongation after fracture and higher high-temperature shrinkage after fracture.
[0065] Preferably, the elongation after fracture of the 3D printed part at 650° C. is ≥18%, and the shrinkage after fracture of the 3D printed part is ≥25%.
[0066] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0067] Example 1
[0068] The chemical composition of the aging-hardened high-temperature alloy powder for 3D printing provided in this embodiment is as follows by mass percentage: C 0.018%, Cr 16.63%, Mo 5.32%, Nb 3.99%, Ti 0.42%, Al 1.62%, Fe 13.89%, V0.46%, Cu 0.61%, Mn 0.0029%, Si 0.039%, Zr 0.2%, Ce 0.0005%, B 0.002%, S0.0007%, P 0.004%, and the balance is Ni.
[0069] The preparation method of aging-hardened high-temperature alloy powder for 3D printing provided in this embodiment includes the following steps: after the ingredients are prepared according to the above-mentioned components and mass percentages, they are loaded into a smelting furnace, and the smelting furnace is evacuated to a vacuum degree of 8 Pa; the medium frequency voltage is adjusted to perform vacuum smelting until the melt temperature reaches 1680°C, and the smelting time is 70 minutes; refining and degassing are performed; the tundish heating system of the atomizing device is turned on, and high-purity argon gas is introduced at a pressure of 38 MPa, and the molten metal is poured into the tundish and enters the guide pipe and the nozzle, at which time the melt flow is atomized by the high-pressure gas flow, and atomized powder spraying is performed; the powder is collected after cooling to obtain aging-hardened high-temperature alloy powder for 3D printing.
[0070] The aging-hardened high-temperature alloy powder for 3D printing prepared above was used to prepare the sample by selective laser melting 3D printing method using the following parameters: laser power of 283W, laser scanning speed of 990mm / s, laser energy density of 65J / mm 3 , the scanning interval is 0.11mm, and the powder layer thickness is 0.04mm.
[0071] Example 2
[0072] The chemical composition of the aging-hardened high-temperature alloy powder for 3D printing provided in this embodiment is as follows by mass percentage: C 0.023%, Cr 16.41%, Mo 5.24%, Nb 4.02%, Ti 0.43%, Al 1.54%, Fe 13.97%, V0.44%, Cu 0.51%, Mn 0.003%, Si 0.07%, Zr 0.089%, Ce 0.0005%, B 0.002%, S0.0005%, P 0.004%, and the balance is Ni.
[0073] The preparation method of the aging-hardened high-temperature alloy powder for 3D printing and the 3D printing method and parameters provided in this embodiment are the same as those in Example 1.
[0074] Example 3
[0075] The chemical composition of the aging-hardened high-temperature alloy powder for 3D printing provided in this embodiment is as follows by mass percentage: C 0.022%, Cr 16.50%, Mo 5.34%, Nb 3.56%, Ti 0.42%, Al 1.56%, Fe 13.95%, V0.45%, Cu 0.51%, Mn 0.0034%, Si 0.047%, Zr0.092%, Ce 0.0005%, B 0.002%, S0.0006%, P 0.004%, and the balance is Ni.
[0076] The preparation method of the aging-hardened high-temperature alloy powder for 3D printing and the 3D printing method and parameters provided in this embodiment are the same as those in Example 1.
[0077] Example 4
[0078] The chemical composition, dosage, and preparation method of the aging-hardened high-temperature alloy powder for 3D printing provided in this embodiment are the same as those in Example 1.
[0079] The 3D printing method and parameters provided in this embodiment are basically the same as those in Embodiment 1, except that the laser power is replaced with 285W, the laser scanning speed is replaced with 960mm / s, and the laser energy density is replaced with 67J / mm 3 .
[0080] Example 5
[0081] The chemical composition, dosage, and preparation method of the aging-hardened high-temperature alloy powder for 3D printing provided in this embodiment are the same as those in Example 1.
[0082] The 3D printing method and parameters provided in this embodiment are basically the same as those in Embodiment 1, except that the laser power is replaced with 287W, the laser scanning speed is replaced with 945mm / s, and the laser energy density is replaced with 69J / mm 3 .
[0083] Example 6
[0084] The chemical composition, dosage, and preparation method of the aging-hardened high-temperature alloy powder for 3D printing provided in this embodiment are the same as those in Example 1.
[0085] The 3D printing method and parameters provided in this embodiment are basically the same as those in Embodiment 1, except that the laser power is replaced with 275W, the laser scanning speed is replaced with 1096mm / s, and the laser energy density is replaced with 57J / mm 3 .
[0086] Example 7
[0087] The chemical composition, dosage, and preparation method of the aging-hardened high-temperature alloy powder for 3D printing provided in this embodiment are the same as those in Example 1.
[0088] The 3D printing method and parameters provided in this embodiment are basically the same as those in Embodiment 1, except that the laser power is replaced with 301W, the laser scanning speed is replaced with 937mm / s, and the laser energy density is replaced with 73J / mm 3 .
[0089] Comparative Example 1
[0090] The chemical composition of the aging-strengthened high-temperature alloy powder for 3D printing provided in this comparative example is as follows by mass percentage: C 0.016%, Cr 16.48%, Mo 4.34%, Nb 5.09%, Ti 0.8%, Al 0.93%, Fe 13.75%, V0.44%, Cu 0.56%, Mn 0.002%, Si 0.057%, Zr 0.002%, Ce 0.0005%, B 0.0002%, S0.0006%, P 0.004%, and the balance is Ni.
[0091] The preparation method of the aging-hardened high-temperature alloy powder for 3D printing and the 3D printing method and parameters provided in this comparative example are the same as those in Example 1.
[0092] Comparative Example 2
[0093] The chemical composition of the aging-strengthened high-temperature alloy powder for 3D printing provided in this comparative example is as follows by mass percentage: C 0.017%, Cr 16.40%, Mo 4.50%, Nb 4.92%, Ti 0.79%, Al 0.99%, Fe 14.02%, V0.46%, Cu 0.57%, Mn 0.002%, Si 0.044%, Zr 0.002%, Ce 0.0005%, B 0.002%, S0.0006%, P 0.004%, and the balance is Ni.
[0094] The preparation method of the aging-hardened high-temperature alloy powder for 3D printing and the 3D printing method and parameters provided in this comparative example are the same as those in Example 1.
[0095] Experimental Example 1
[0096] The samples obtained after 3D printing in the above embodiments and comparative examples were heat treated (980°C*1h / air cooling+730°C*15h / air cooling+650°C*10h / air cooling), and then the heat-treated samples were processed into standard tensile specimens by wire cutting. The room temperature tensile properties of each sample were tested using an electronic universal material testing machine. The test results are shown in Table 1.
[0097] Table 1 Test results of plasticity and strength properties of each sample at different temperatures
[0098]
[0099]
[0100]
[0101] As can be seen from Table 1, the samples prepared in Examples 1 to 7 have higher elongation and contraction after fracture, as well as higher tensile strength and yield strength. However, the tensile plasticity of Comparative Examples 1 and 2 is relatively low, especially the high-temperature plasticity is significantly low. It can be seen that the aging-strengthened high-temperature alloy powder for 3D printing with a specific chemical composition provided by the present invention improves tensile plasticity, especially high-temperature tensile plasticity.
[0102] At the same time, by comparing the experimental data of Example 1, Example 6 and Example 7, it can be seen that the parameters of 3D printing have a great influence on the strength performance, and will also affect the tensile plasticity to a certain extent.
[0103] Furthermore, the tissue morphology of the sample obtained by 3D printing in Example 1 is as follows Figure 1 The morphology of the sample obtained by 3D printing in Example 2 is shown in Figure 2 The morphology of the sample obtained by 3D printing in Example 3 is shown in Figure 3 The microstructure of the sample obtained by 3D printing in Comparative Example 1 is shown in Figure 4 The microstructure of the sample obtained by 3D printing in Comparative Example 2 is shown in Figure 5 shown.
[0104] By comparing the organizational morphology diagrams of the samples of Example 1, Comparative Example 1 and Comparative Example 2 and the experimental results in Table 1, it can be seen that the distribution of carbides on the grain boundaries in Comparative Example 1 and Comparative Example 2 presents a continuous chain distribution and the blocks are relatively large, which has an adverse effect on the tensile plasticity of the alloy.
[0105] By comparing the organizational morphology diagrams of the samples of Examples 1 to 3 and the experimental results in Table 1, it can be seen that in Examples 1 to 3, the grain boundary carbides are distributed in discontinuous blocks, which has a favorable effect on the tensile plasticity of the alloy.
[0106] Furthermore, the sample obtained by 3D printing in Example 1 was ground and polished along the transverse section, cleaned and then observed for defects using an optical microscope. The results are as follows: Figure 6 The sample obtained by 3D printing in Example 4 was ground and polished along the transverse section, and then cleaned and observed for defects using an optical microscope. The results are as follows: Figure 7 The sample obtained by 3D printing in Example 5 was ground and polished along the transverse section, and then cleaned and observed for defects using an optical microscope. The results are as follows: Figure 8 The sample obtained by 3D printing in Example 6 was ground and polished along the transverse section, and then cleaned and observed for defects using an optical microscope. The results are as follows: Fig. 9 The sample obtained by 3D printing in Example 7 was ground and polished along the transverse section, and then cleaned and observed using an optical microscope for defects. The results are as follows Fig.10 shown.
[0107] from Figure 6 to Figure 8 It can be seen that the samples prepared in Example 1, Example 4 and Example 5 have lower porosity, smaller pore size and fewer defects. Fig. 9 ), when the laser power is low, the laser scanning speed is high and the laser energy density is low, the powder does not absorb enough laser energy, and there may be incomplete melting, and there are many defects such as holes and unmelted inclusions in the molded sample. Example 7 ( Fig.10 ), when the laser power is high, the laser scanning speed is low and the laser energy density is high, the powder absorbs too much energy, which may cause pores, oxidation or overburning, and the surface quality is reduced.
[0108] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. Aging-hardened high-temperature alloy powder for 3D printing, characterized in that: The chemical composition of the aging-strengthening high-temperature alloy powder for 3D printing includes, by mass percentage, C≤0.05%, Cr 14.5%-18.5%, Mo 5.2%-6.0%, Nb 3.5%-4.5%, Ti 0.1%-0.7%, Al1.2%-2.0%, Fe 12%-16%, V 0.3%-0.6%, Cu 0.1%-1.0%, Mn≤0.5%, Si≤0.5%, Zr 0.2%-0.3%, Ce≤0.01%, B≤0.01%, S≤0.015%, P≤0.015%, and the balance is Ni.
2. The aging-hardened high-temperature alloy powder for 3D printing according to claim 1, characterized in that: The chemical composition of the aging-strengthening high-temperature alloy powder for 3D printing includes, by mass percentage, C≤0.05%, Cr 14.5%-18.5%, Mo 5.2%-6.0%, Nb 3.5%-4.5%, Ti 0.1%-0.6%, Al 1.2%-2.0%, Fe12%-16%, V 0.3%-0.6%, Cu 0.6%-1.0%, Mn≤0.5%, Si≤0.5%, Zr 0.2%-0.3%, Ce≤0.01%, B≤0.01%, S≤0.015%, P≤0.015%, and the balance is Ni.
3. The aging-hardened high-temperature alloy powder for 3D printing according to claim 1, characterized in that: The chemical composition of the aging-strengthening high-temperature alloy powder for 3D printing includes, by mass percentage, C≤0.05%, Cr 14.5%-18.5%, Mo 5.2%-6.0%, Nb 3.5%-4.1%, Ti 0.1%-0.5%, Al 1.2%-1.6%, Fe12%-16%, V 0.3%-0.6%, Cu 0.6%-1.0%, Mn≤0.5%, Si≤0.5%, Zr 0.2%-0.3%, Ce≤0.01%, B≤0.01%, S≤0.015%, P≤0.015%, and the balance is Ni.
4. The method for preparing aging-hardened high-temperature alloy powder for 3D printing according to any one of claims 1 to 3, characterized in that: The steps include: After being prepared according to the mass percentages described in any one of claims 1 to 3, the prepared metal powder is subjected to vacuum melting to obtain molten metal liquid; The molten metal liquid is atomized and powdered to obtain the aging-strengthened high-temperature alloy powder for 3D printing.
5. The method for preparing aging-hardened high-temperature alloy powder for 3D printing according to claim 4, characterized in that: The temperature of the vacuum melting is 1670-1690°C.
6. The method for preparing aging-hardened high-temperature alloy powder for 3D printing according to claim 4, characterized in that: The vacuum degree during the vacuum melting process is 7-9Pa.
7. The method for preparing aging-hardened high-temperature alloy powder for 3D printing according to claim 4, characterized in that: The gas atomization pressure during the atomization powder spraying process is 3.7-3.9 MPa.
8. The 3D printing method of the aging-hardened high-temperature alloy powder for 3D printing according to any one of claims 1 to 3, characterized in that: The 3D printing includes laser powder bed fusion additive manufacturing.
9. The 3D printing method of aging-hardened high-temperature alloy powder for 3D printing according to claim 8, characterized in that: The laser power of the 3D printing is 280-290W.
10. The 3D printing method of aging-hardened high-temperature alloy powder for 3D printing according to claim 8, characterized in that: The laser scanning speed of the 3D printing is 940-990 mm / s.
11. The 3D printing method of aging-hardened high-temperature alloy powder for 3D printing according to claim 8, characterized in that: The laser energy density of the 3D printing is 65-70 J / mm 3 .
12. A 3D printed part obtained by the 3D printing method of aging-hardened high-temperature alloy powder for 3D printing as claimed in any one of claims 8 to 11.
13. The 3D printed part according to claim 12, characterized in that: The elongation after fracture of the 3D printed part at 650° C. is ≥13%, and the shrinkage after fracture of the 3D printed part is ≥22%.
14. The 3D printed part according to claim 12, characterized in that: The elongation after fracture of the 3D printed part at 650° C. is ≥18%, and the shrinkage after fracture of the 3D printed part is ≥25%.
Citation Information
Patent Citations
Nickel-based alloy resistant to high temperature oxidation
CN105838925A
High-temperature alloy for hydrogen fuel cell air compressor bearing, and preparation method thereof
CN111733346A
Heat treatment method for additive manufacturing high-temperature alloy working in oxygen-enriched high-temperature environment
CN114643368A